Indo-European poetry and myth - West, M. L. (Martin Litchfield), 1937- (New York : Oxford University Press, 2007)
The Indo-Europeans, speakers of the prehistoric parent language from which most European and some Asiatic languages are descended, most probably lived on the Eurasian steppes some five or six thousand years ago. Martin West investigates their traditional mythologies, religions, and poetries, and points to elements of common heritage. In The East Face of Helicon (1997), West showed the extent to which Homeric and other early Greek poetry was influenced by Near Eastern traditions, mainly non-Indo-European. His new book presents a foil to that work by identifying elements of more ancient, Indo-European heritage in the Greek material. Topics covered include the status of poets and poetry in Indo-European societies; metre, style, and diction; gods and other supernatural beings, from Father Sky and Mother Earth to the Sun-god and his beautiful daughter, the Thunder-god and other elemental deities, and earthly orders such as Nymphs and Elves; the forms of hymns, prayers, and incantations; conceptions about the world, its origin, mankind, death, and fate; the ideology of fame and of immortalization through poetry; the typology of the king and the hero; the hero as warrior, and the conventions of battle narrative.
1., Poet and Poesy -- 2., Phrase and Figure -- 3., Gods and Goddesses -- 4., Sky and Earth -- 5., Sun and Daughter -- 6., Storm and Stream -- 7., Nymphs and Gnomes -- 8., Hymns and Spells -- 9., Cosmos and Canon -- 10., Mortality and Fame -- 11., King and Hero -- 12., Arms and the Man
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: indoevropské mytologie; starověké civilizace -- Eurasie; poezie -- Eurasie; indoevropeistika; indoevropské jazyky; Indo-European mythology; ancient civilization -- Eurasia; poetry -- Eurasia; Indo-European studies; Indo-european languages; monografie; e-knihy online; monographs; e-books online